Skin surface lipidomics revealed the correlation between lipidomic profile and grade in adolescent acne. (20th April 2020) - Zhou, Mingyue; Yang, Manli; Zheng, Yumei; Dong, Kun; Song, Liya; He, Congfen; Liu, Wei; Wang, Yiyu; Jia, Yan
Abstract: Background: Acne is a multifactorial skin disorder frequently observed during adolescence with different grades of severity. The crucial factors of acne are the increase of lipids secretion and the change of composition on the skin surface lipid (SSL). However, there are no studies on the changes of lipid composition and content between different grades of adolescent acne in lesional skin and nonlesionsal skin. Aims: This study was to investigate correlation in the composition of SSL and different grades in order to understand the tendency of SSL alterations in this disease for successful acne management and prevention. Methods: A powerful analytical technique, UPLC‐QTOF‐MS, and multivariate data analysis were used to investigate SSL variations of lipid main classes, subclasses, and species. Results: The results indicated that sphinganine, triradylglycerols (TG), and phytosphingosine were important in adolescent acne development. The average fatty acids (FAs) chain length in patients with acne showed significantly shortened trend from mild to moderate adolescent acne. Additionally, the relative average content of TG, diglyceride (DG), FA, ceramides (Cers), and the level of unsaturated FAs significantly increased from mild to moderate adolescent acne. Interestingly, our results demonstrated that the phytosphingosine and sphinganine showed an increasing trend in mild acne groups, but decreasing trend in lesional skin of moderate group. Conclusions: Lipidomics analysis suggested that the variation of TG, phytosphingosine, and sphinganine was closely related to the occurrence severity of acne in adolescent.